The Effectiveness of Blended Learning in Teaching English Based on the ICT - Muliaty Ibrahim; Yulini Rinantanti (Universitas Cokroaminoto Palopo, 2023)
This research aimed to describe the effectiveness of Blended Learning in teaching English. This research was qualitative that focused on evaluating learning using Blended Learning. The data collection techniques used in this research were observation, questionnaires by using the google form application, and unstructured interviews. The results of the research were obtained and analyzed qualitatively. Based on the results Blended learning had more effective than online learning and face-to-face in terms of the student’s learning outcomes. The use of Blended learning can be applied by doing 50/50, which means 50% of online and offline learning, 50% face-to-face learning, 75/25, 75% online and offline learning, 25% face-to-face learning, or 25/75, 25% online learning. and offline 75% face-to-face learning with the location of the learning time.